Effect of Participations of Frames in Dual System on Development of Fragility Curves - تريكية علي; منصور نزيه; دبول غنوة (Latakia University Journal -Engineering Sciences Series, 2020)
This paper presents a study of four R/C buildings, where the buildings had dual systems and frame systems where the participations of frames to resist the shear force are 78%, 44% and 28%, 17%. These buildings are designed by Syrian Code and in this study it will studying by nonlinear static analysis where The performance points and capacity curves are calculated and the Results of pushover analysis are used to development fragility curves for damage states. The results of study showed that the reduction of participations of frames are caused a decrease in the probability of seismic damage in building as long as the frames contribution rate is not less than 28%.